A data-driven frequency criteria assessment by determining system minimum level of inertia - Kyungsang Lee; Seunghyuk Im; Byongjun Lee (Energy Reports, 2023)
The generation of inverter-based renewable energy affects system frequency and is limited by frequency criteria. In a power system with two or more criteria, it is important to understand whether the frequency criteria are appropriate because these should not differ in terms of renewable energy generation for consistent power operation. This study proposes a method to evaluate the frequency criteria applied to the system operation data by determining the minimum level of inertia required for the latter according to the effect of renewable energy generation. The minimum level of inertia can be determined as the minimum inertia value that satisfies the frequency criteria when inertia and frequency regulating reserve change with the operation of the generator. The minimum level of inertia was determined by conducting a frequency simulation by applying two frequency criteria in Korea. The proposed methodology has been applied to 7080 operation data, when two maximum output generators are operating more than 1400 MW simultaneously, out of 23003 time-based data extracted from the Energy Management System (EMS). Further, from the results, the minimum level of inertia for the N-1 frequency criterion was higher than the generator N-2 frequency criterion. This result indicates that the N-1 frequency criterion is more conservative in terms of the accommodation of renewable energy than the N-2 frequency criterion and that renewable energy will be limited by the N-1 frequency criterion. An important finding of this study is that the two frequency criteria in South Korea are applied differently in terms of the minimum level of inertia.